MATHEMATICAL CONNECTION ABILITY VIEWED FROM THE ADVERSITY QUOTIENT IN THE REACT LEARNING MODEL - Nura Milla Husna; Mulyono Mulyono; Detalia Noriza Munahefi (Universitas Muhammadiyah Metro, 2026)
This study aims to describe students' mathematical connection abilities in terms of adversity quotient types in the REACT learning model assisted by the Salatiga cultural ethnomathematics e-module. The research method uses a mixed method with an explanatory design. The population in this quantitative study was all VIII grade students of SMP N 10 Salatiga in the 2025/2025 academic year. The research sample was taken by cluster random sampling and obtained class VIII-H. The research subjects were taken based on the adversity quotient type using a purposive sampling technique in class VIII-H. The results of the study indicate that (1) adversity quotient has a positive effect on students' mathematical connection abilities, and (2) descriptions of mathematical connection abilities in terms of AQ in REACT learning assisted by the Salatiga cultural ethnomathematics e-module with a wordwall can be seen from each category of AQ types. Subjects with AQ climbers were able to fulfill three indicators of mathematical connections, namely 1) the connection between mathematics and real life, 2) the connection between mathematical materials, and 3) the connection between mathematics and other disciplines. Subjects with AQ campers were able to fulfill two indicators of mathematical connections, namely 1) the connection between mathematics and real life and 2) the connection between mathematical materials. Meanwhile, subjects with AQ quitters were only able to fulfill one indicator, namely 1) the connection between mathematics and real life. Penelitian ini bertujuan untuk mendeksripsikan kemampuan koneksi matematis peserta didik ditinjau dari tipe adversity quotient pada model pembelajaran REACT berbantuan e-modul etnomatematika budaya Salatiga. Metode penelitian menggunakan mixed method dengan desain explanatory design. Populasi pada penelitian kuantitatif adalah seluruh kelas VIII SMP N 10 Salatiga tahun ajaran 2025/2025. Sampel penelitian diambil dengan cluster random sampling dan diperoleh kelas VIII-H. Subjek penelitian diambil berdasarkan tipe adversity quotient menggunakan teknik purposive sampling pada kelas VIII-H. Hasil penelitian menunjukkan bahwa (1) adversity quotient berpengaruh positif terhadap kemampuan koneksi matematis peserta didik, dan (2) deskripsi kemampuan koneksi matematis ditinjau dari AQ pada pembelajaran REACT berbantuan e-modul etnomatematika budaya Salatiga dengan wordwall dapat dilihat dari masing-masing kategori tipe AQ. Subjek dengan AQ climber mampu memenuhi ketiga indikator koneksi matematis yaitu 1) kaitan matematika dengan kehidupan sehari-hari, 2) kaitan antar materi matematika, dan 3) kaitan matematika dengan disiplin ilmu lain. Subjek dengan AQ campers mampu memenuhi dua indikator koneksi matematis 1) kaitan matematika dengan kehidupan sehari-hari dan 2) kaitan antar materi matematika. Sedangkan pada subjek dengan AQ quitter hanya mampu memenuhi satu indikator saja yaitu 1) kaitan matematika dengan kehidupan sehari-hari.